Mitigation of radiation exposure during surgical hepatectomy after yttrium-90 radioembolization. (19th August 2021) - Decoteau, Mary A; Steuterman, Steven; Kurian, Sunil M; Case, Jamie; Lewis, Paul R; Fisher, Jonathan S; Schaffer, Randolph L; Marsh, Christopher L
Abstract: Yttrium-90 (Y-90) radioembolization for the treatment of hepatocellular carcinoma can present safety challenges when transplanting recently treated Y-90 patients. To reduce surgeons' contact with radioactive tissue and remain within occupational dose limits, current guidelines recommend delaying transplants at least 14 days, if possible. We wanted to determine the level of radiation exposure to the transplant surgeon when explanting an irradiated liver before the recommended decay period. An ex-vivo radiation exposure analysis was conducted on the explanted liver of a patient who received Y-90 therapy 46 h prior to orthotopic liver transplant. To estimate exposure to the surgeon's hands, radiation dosimeter rings were placed inside three different surgical glove configurations and exposed to the explanted liver. Estimated radiation doses corrected for Y-90 decay were calculated. Radiation safety gloves performed best, with an average radiation exposure rate of 5.36 mSV h −1 in the static hand position, an 83% reduction in exposure over controls with no glove (31.31 mSv h −1 ). Interestingly, non-radiation safety gloves also demonstrated reduced exposure rates, well below occupational regulation limits. Handling of Y-90 radiated organs within the immediate post-treatment period can be done safely and does not exceed federal occupational dose limits if appropriate gloves and necessary precautions are exercised.